2017
DOI: 10.1111/pops.12393
|View full text |Cite
|
Sign up to set email alerts
|

The Principle‐Implementation Gap in Attitudes Towards Racial Equality (and How to Close It)

Abstract: Research on attitudes towards racial equality has identified an apparent paradox, sometimes described as the “Principle‐Implementation Gap.” White Americans accept equality as an ideal yet reject interventions designed to achieve that ideal. In this article, we provide a critical review of empirical and theoretical work in the field and outline some directions for future research. Drawing on a program of research conducted in post‐apartheid South Africa, we argue for the value of: (1) widening the field beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 115 publications
5
40
0
Order By: Relevance
“…Support for our hypotheses was especially provided by perceptions of legitimacy: quantity and quality of contact were associated with reduced perceptions that the system is legitimate; in turn, greater illegitimacy perceptions were associated with stronger intentions to engage in actions for social change. Note that we had also acknowledged the possibility that contact would be associated with greater perceived legitimacy, in line with research arguing for a sedative effect of contact, but in contrast with the majority of research showing that, among advantaged group members, contact is associated with greater support for social change on behalf of disadvantaged groups (Dixon, Durrheim, & Thomae, 2017). In fact, supporting the beneficial effect of contact on social change motivation for the advantaged, this does not appear to be the case: the fact that contact is associated with stronger awareness of stability of the system does not seem to be in contrast with awareness of societal injustices, which in this study was found to be the determinant of one’s intentions to act to support intergroup equality.…”
Section: Discussionsupporting
confidence: 77%
“…Support for our hypotheses was especially provided by perceptions of legitimacy: quantity and quality of contact were associated with reduced perceptions that the system is legitimate; in turn, greater illegitimacy perceptions were associated with stronger intentions to engage in actions for social change. Note that we had also acknowledged the possibility that contact would be associated with greater perceived legitimacy, in line with research arguing for a sedative effect of contact, but in contrast with the majority of research showing that, among advantaged group members, contact is associated with greater support for social change on behalf of disadvantaged groups (Dixon, Durrheim, & Thomae, 2017). In fact, supporting the beneficial effect of contact on social change motivation for the advantaged, this does not appear to be the case: the fact that contact is associated with stronger awareness of stability of the system does not seem to be in contrast with awareness of societal injustices, which in this study was found to be the determinant of one’s intentions to act to support intergroup equality.…”
Section: Discussionsupporting
confidence: 77%
“…However, this inclusive representation was not related to more complex immigration‐related cognitions, behavioral intentions, and immigration policies with implications for North African immigrants and immigrants in general. Such seemingly paradoxical results are in accordance with evidence of differences in measure sensitivity (e.g., Tropp & Pettigrew, ) and with a principle–implementation gap (Dixon, Durrheim, & Thomae, ) indicating that ingroup members may report idealized preferences for equality and social inclusion (e.g., liking of immigrants), but such preferences need not translate into favoring policies aiming to achieve inclusion. Study 2 showed that high national identity centrality (Leach et al., ) was associated with negative views about the social impact of immigrants, and with higher preference toward policies aiming to exclude immigrants from society.…”
Section: Discussionsupporting
confidence: 77%
“…An important reason for intergroup toleration is the endorsement of civil equality and liberties such as freedom of thought and expression (Scanlon, ). However, there is often a clear difference in the way in which people judge abstract principles in comparison to concrete cases or situations (Dixon, Durrheim, & Thomae, ). It is one thing to agree with the ideal of freedom of speech, but another to accept a government official who burns the Quran or an imam who dubs homosexuals as inferior people.…”
Section: Reasons For Tolerancementioning
confidence: 99%